2016
DOI: 10.34257/gjmbrevol22is2pg35
|View full text |Cite
|
Sign up to set email alerts
|

Travel from Traditional Marketing to Digital Marketing

Abstract: Lately, with the information technology improvements and broad band internet service spreading, speed of access to shopping sites get high. Because of these changes, companies unavoidably entered to digital environment. Thus, while communication rules change, field and definition of marketing changes too. With the development of IT technologies, traditional marketing methods leave sits place to digital day by day. Companies which follow technology can easily communicate with customers interactively while provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 2 publications
0
27
0
2
Order By: Relevance
“…In the non-digital (traditional) marketing strategy, film promotion is generally conducted by exhibiting a movie trailer in theaters or paid advertising in newspapers and magazines. However, the current advertising practice has utilized websites for promoting films (Durmaz & Efendioglu, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the non-digital (traditional) marketing strategy, film promotion is generally conducted by exhibiting a movie trailer in theaters or paid advertising in newspapers and magazines. However, the current advertising practice has utilized websites for promoting films (Durmaz & Efendioglu, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…An economy aims at growth which indirectly or directly motivates startups growth as well. Strategies [40] such entrepreneurs struggle to market their unique strategic ideas into the platform ahead of customers with the fear of lack of funding that would incur losses. Marketing transformational change has helped them be confident and implement ideas with less funds and more benefits [41].…”
Section: Digital Marketing Strategiesmentioning
confidence: 99%
“…Fig. 1: Aim of Traditional Marketing Source: Durmaz, Y., & Efendioglu, I. H. (2016) [40]. Traditional marketing aims for working within one's comfort zone whereas, marketers aim for doing something extraordinary that is not within the boundaries of comfort zone.…”
mentioning
confidence: 99%
“…Online advertising utilizing social media, networking sites, emails, mobile phone texts, and applications (apps) opened the door for Ecommerce (Dwivedi et al, 2021). Durmaz and Efendioglu (2016) reported that customers through digital marketing easily and quickly reach their needs from products. Therefore, researchers developed quantitative and qualitative key performance indicators for digital marketing in order to achieve a consensus on the use and measurement of these indicators (Saura et al, 2017).…”
Section: Digital Marketingmentioning
confidence: 99%